Dynamique du peuplement ligneux dans un parcours agrosylvopastoral du Sénégal - Oumar Sarr; Daouda Ngom; Amy Bakhoum; Léonard E. Akpo (VertigO)
This study evaluates the dynamic of woody vegetation in the Kaffrine community course from the time of the great Sahelian droughts to this current period. The methodology uses ethnobotanical surveys applied to residents and transhumant belonging in selected villages.their Content addressed aspects related to the state of ligneous populating and its evolutions between 1973-2012. The results show up an increasing degradation of the environment with a significant loss of biodiversity, marked by the disappearance of some families and a scarceness of the genera and species number. Combretaceae’s family resists better with a good recovery despite a great deal of restrictions. For multiple functions insured by tree in these courses, it is important to think more of sustainable means of management with local communities in order to rehabilitate and preserve these ecosystems.